La tradition orale et les savoirs artisanaux (1re partie) - Genest, Bernard (Ethnologies, 2001)
In this historiographic account, the author distinguishes between two different voices in the development of folklore as a discipline in Québec. Since the beginning of folklore studies in 19th century thinking, researchers have divided in two camps: exponents of oral tradition (seen as a heritage on its way to extinction), and exponents of material culture. This divergence can be seen in the work of Edouard Massicotte, Marius Barbeau, J.M. Gauvreau and Robert-Lionel Séguin. With the work of Luc Lacourcière, folklore began to be seen as an indivisible whole. Looking at the careers of the main figures in the discipline, the author shows how their perspectives eventually meet in a new approach.